Analisa Kualitas Pelayanan di Departemen Teknik Kimia Industri, Fakultas Vokasi ITS Surabaya dalam perspektif Higher Education Performance (HEdPerf) - Yuli Purwanto; Wawan Prawono; Ratri Wandha Kirana (Institut Teknologi Sepuluh Nopember, 2022)
The purpose of this study was to measure the performance of service quality by using students' perceptions of service quality performance at the Department of Industrial Chemical Engineering, Faculty of Vocational Studies ITS Surabaya Indonesia through the Higher Education Performance (HEdPerf) measurement scale using six structural dimensions consisting of Non-Academic Aspects, Academic Aspects, Reputation, Access, Program Issues, and Understanding. Quantitative descriptive method, questionnaire survey with Probability Sampling technique, and Proportioned Stratified Random Sampling collecti0n technique were used as methods in this study. The results of the analysis using Importance-Performance Analysis show the similarity of the measurement results between each service item measurement and the measurement of the factor/dimensional structure instrument. The reputation factor is a top priority for improving service quality. Academic and Access factors have service quality that must be maintained. Understanding Program Factors and Problems is the second priority for improving service quality. Then non-academic factors indicate that the quality of service exceeds student expectations